Entre classe d’inclusion et Unité Localisée pour l’Inclusion Scolaire en lycée professionnel : suivis ethnographiques d’une scolarisation adaptée - Godefroy Lansade (Recherches en Éducation)
This research is based on an ethnographic observation conducted with a group of adults and young teenagers, called mentally handicapped school attending a vocational high school within a ULIS scheme. She questions and analyzes the experiences that these students have this scheme attached to inclusive education. After recalling some of the great moments of inclusive education within secondary education, and considering this new paradigm on three scales -physical, social and epistemic- we’ll see how this scheme differs from a class. The study shows that to be attached simultaneously to an inclusive classroom and the scheme may cause unexpected paradoxical situations. Therefore the ULIS appears as inoperative or against-productive scheme under the issues displayed of inclusion.